2
$\begingroup$

Find: $$\lim_{x\to0^-}\frac{\sqrt{x^4\cos^2{x}+2x^2\sin^2{2x}-x^4}}{x^2}\cdot$$

I tried to simplify the expression, but I kept getting stuck. I also tried to make a substitution $u=\frac{1}{x}$, but I got stuck again. Please give me hint or explain what to do. Thanks.

$\endgroup$
3
$\begingroup$

$$\lim_{x\to0^-}\frac{\sqrt{x^4\cos^2{x}+2x^2\sin^2{2x}-x^4}}{x^2}$$ $$=\lim_{x\to0^-}\sqrt{\cos^2{x}+\frac{8\sin^2{2x}}{(2x)^2}-1}$$ $$=\sqrt{8}$$ $$=2\sqrt{2}$$

$\endgroup$
2
$\begingroup$

Factor by $x^4$ inside the square root and simplify by $x^2$.

then using the classical limit $$\lim_0\frac {\sin (X)}{X}=1$$

we get $$2\sqrt {2} $$

$\endgroup$
0
$\begingroup$

$$\frac{\sqrt{x^4\cos^2{x}+2x^2\sin^2{2x}-x^4}}{x^2} = \frac{\sqrt{x^4\cos^2{x}+8x^2 \sin^2x \cos^2x-x^4}}{x^2}= \frac{\sqrt{x^4(\cos^2{x}-1)+8x^2 \sin^2x \cos^2x}}{x^2}= \frac{\sqrt{-x^4\sin^2 x+8x^2 \sin^2x \cos^2x}}{x^2} = \frac{\sqrt{x^2\sin^2 x(8 \cos^2x - x^2)}}{x^2} = \frac{\sqrt{\sin^2 x(8 \cos^2x - x^2)}}{x} = \sqrt{ \left(\frac{\sin x}{x}\right)^2 (8 \cos^2x - x^2)} $$ Now, take the limit $$\lim_{x\rightarrow 0^{-}}\sqrt{ \left(\frac{\sin x}{x}\right)^2 (8 \cos^2x - x^2)} = \lim_{x\rightarrow 0^{-}}\sqrt{ \left(\frac{\sin x}{x}\right)^2} \lim_{x\rightarrow 0^{-}}\sqrt{(8 \cos^2x - x^2)} = 1 \times \sqrt{8} = 2\sqrt{2}$$

$\endgroup$
0
$\begingroup$

Note that, as $x \to 0$, we have $$ \sin x \sim x \implies\sin^2(2x)\approx4x^2 \\ \cos x \sim1 \implies\cos^2(x)\approx1 $$ We can use these to greatly simplify the limit at hand: $$\lim_{x \to 0}\frac{\sqrt{x^4\cos^2{x}+2x^2\sin^2{2x}-x^4}}{x^2}=\lim_{x \to 0}\frac{\sqrt{8x^4}}{x^2} = \color{red}{\sqrt 8}$$

If you want a mor rigorous proof, we can instead use squeeze theorem or $O$ notation. Using the latter, we can write $\sin^2(2x) \in 4x^2 + O(x^6)$ and $\cos^2(x) \in 1+O(x^4)$ as $x \to 0$, giving us

$$\begin{align} \lim_{x \to 0}\frac{\sqrt{x^4\cos^2{x}+2x^2\sin^2{2x}-x^4}}{x^2} &=\lim_{x \to 0}\frac{\sqrt{x^4[1+O(x^4)]+2x^2[4x^2+O(x^6)]-x^4}}{x^2} \\&=\lim_{x \to 0}\frac{\sqrt{x^4+8x^4+O(x^8)-x^4}}{x^2} \\&=\lim_{x \to 0}\sqrt{\frac{8x^4+O(x^8)}{x^4}} \\&=\lim_{x \to 0}\sqrt{8+O(x^4)} \\&=\sqrt{8+\lim_{x \to 0}O(x^4)} \\&= \color{red}{\sqrt 8} \end{align}$$

$\endgroup$
0
$\begingroup$

Just added as a too long comment.

Many ways to get the answer have been given in answers. Using Taylor expansions with one more term, you could even know how is approached the limit since $$x^4 \cos ^2(x)+2 x^2 \sin ^2(2 x)=9 x^4-\frac{35 x^6}{3}+O\left(x^8\right)$$ making $$x^4 \cos ^2(x)+2 x^2 \sin ^2(2 x)-x^4=8 x^4-\frac{35 x^6}{3}+O\left(x^8\right)$$ $$\sqrt{x^4 \cos ^2(x)+2 x^2 \sin ^2(2 x)-x^4}=2 \sqrt{2}\, x^2-\frac{35 }{12 \sqrt{2}}x^4+O\left(x^6\right)$$ $$\frac{\sqrt{x^4\cos^2{x}+2x^2\sin^2{2x}-x^4}}{x^2}=2 \sqrt{2}-\frac{35 x^2}{12 \sqrt{2}}+O\left(x^4\right)$$ which shows the limit and how it is approached.

Moreover, this provides an easy estimation of the function "close" to $x=0$. For example $$x=\frac \pi 6 \implies \text{exact} \approx 2.28503 \qquad \text{approximation} \approx 2.26301$$ $$x=\frac \pi 4 \implies \text{exact} \approx 1.65598 \qquad \text{approximation} \approx 1.55624$$

$\endgroup$
  • $\begingroup$ nice explanation $\endgroup$ – Amarildo Jun 4 '17 at 18:14
0
$\begingroup$

The expression in square roots can be simplified as $$8x^{2}\sin^{2}x\cos^{2}x-x^{4}\sin^{2}x$$ and hence the numerator becomes $$x\sin x\sqrt{8\cos^{2}x - x^{2}} $$ and thus we can see that the given expression can be written as $$\frac{\sin x} {x} \cdot\sqrt{8\cos^{2}x-x^{2}}\to 1\cdot \sqrt{8\cdot 1^{2}-0^{2}}=2\sqrt{2}$$ and thus the desired limit is $2\sqrt{2}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.